The effectiveness of micronized powder and crumb rubbers as fine aggregates replacement in ultra-high performance concrete - Azhroul, Bah Piyan (2017)
Ultra-high performance concrete (UHPC) is a relatively new class of advanced construction material and has superior strength. Nowadays, the need to incorporate recycled or waste product as alternative materials in concrete mixture is become interests and great potential to be explored. Previous researches have been studied on the effectiveness of using recycled waste tyres as replacement materials in conventional and high strength concretes. In comparison with previous studies, micro-waste rubber powder (micro WRP) was used as fine aggregate to replace the-conventional sand. As a consequence, this study was focused on the effect of using crumb rubber and microWRP in UHPC mixture. The levels replacement of crumb rubber and micro WRP comprises of 0%, 10%, 20%, 30%, 40% and 50% from the weight of fine aggregate used. To fulfil the utilization of crumb and micro WRP in UPHC, the workability properties and compressive strength of UPHC and a series of UHPC incorporating crumb rubber and miro WRP (rubberized-UHPC) was examined. The compressive strength of UHPC and rubberized-UHPC was tested for 7, 14 and 28 days of curing days. Further, the expected outcome of this study will correlate the effectiveness of incorporating different levels of crumb rubber and microWRP with subjected to the workability properties and compressive strength of rubberized-UHPC has been reviewed. The experiment results revealed that the incorporation of crumb rubber and micro WRP into UHPC mix was leaded to the reduction of workability and compressive strength. In this study found that the increasing the percentage of crumb rubber and micro WRP as partial replacement of sand, decrease the flowabilty of concrete. It can observed that percentage of crumb rubber and micro WRP as replacement of sand are increase, the compressive strength of rubberized are decreasing.